A field survey of crop management practices and distribution of ALS resistant Euphorbia heterophylla in two states in southern Brazil - Vidal,R.A. (2004)
Herbicide resistance was reported in Brazil almost ten years ago. One of the main weeds with herbicide resistance is wild poinsettia (Euphorbia heterophylla). This work evaluates the distribution of ALS-resistant E. heterophylla in two states in southern Brazil and determines the major contributing management causes for weed resistance selection in the area. E. heterophylla seeds from 148 sites located in Paraná and Rio Grande do Sul were sampled during 2001 and 2002. Farmers provided specific site data for weed control, tillage system, crop rotation and harvesting operations during previous years. ALS resistant E. heterophylla biotypes were found widely distributed in the survey area. Data analysis suggests seed dissemination is unlikely to explain the widespread distribution of resistance. The most probable factor for the selection of the resistant E. heterophylla is the persistent high use of ALS-inhibiting herbicides over time. Indirect evidence is presented demonstrating the need to educate legislators and farmers about the importance of herbicide mixtures as a strategy to prevent herbicide resistance.